Are growth-oriented SMEs more likely to adopt market and brand orientations?. Issue 2 (13th May 2014) - Reijonen, Helen; Párdányi, Szandra; Tuominen, Sasu; Laukkanen, Tommi; Komppula, Raija
Abstract : Purpose: – The purpose of this paper is to examine how SMEs with varying growth intentions differ from each other with regard to market orientation and brand orientation. Both of these strategic orientations are seen to lead to enhanced market performance. Consequently, the authors investigate whether those small firms that regard growth as an important goal have adopted market or brand orientation. Design/methodology/approach: – Responses from 492 SMEs were analysed. They were clustered into four groups according to their growth intentions. These groups included firms that have low growth intention, capital adequacy growth intention, expansion growth intention and high growth intention. ANOVA was used to explore whether these groups differed in their market or brand orientation. Findings: – The results indicate that the higher growth intention group the SME belonged to the more market and brand oriented it is. The biggest differences between the SMEs were found with regards to brand orientation. Research limitations/implications: – The findings suggest that SMEs have acknowledged the positive effect of market and brand orientations on firm growth, thus highlighting the importance of supporting growth-oriented SMEs in their quest to become more market or brand oriented. Originality/value: – The study sheds more light on the little researched themes of market and brand orientations in the context of SMEs. It also offers insights into how growth intentions affect the adoption of different strategic orientations.